Dabie bandavirus identified from patients with severe fever with thrombocytopenia syndrome in northwestern of Hubei Province, China, 2024 - Zhang, Mengzhu; Fu, Peixi; Meng, ZhongJi; He, Yuqian; Qin, Xueqin; Luo, Sen; Xu, Yunzhen; Liu, Li; Qiu, Guangyu; Liu, Yang; Peng, Yanli; Song, Fangmin; et al. (Frontiers in Public Health, 2025)
IntroductionSevere fever with thrombocytopenia syndrome (SFTS), caused by Dabie bandavirus (DBV), is a zoonotic disease characterized by substantial mortality. Hubei Province is an epidemic region with a high incidence rate of SFTS. The clinical manifestations and case fatality rates (CFRs) of SFTS correlate with specific geographic regions and genotypes of DBV.MethodsFrom January to December 2024, serum samples were obtained from 69 patients with suspected DBV infection in northwestern Hubei Province, China. The presence of DBV RNA was used as the diagnostic criterion for SFTS. Demographic characteristics, clinical manifestations, and laboratory findings of confirmed SFTS patients were systematically collected. Phylogenetic analyses of the DBV L, M, and S gene segments were performed using the maximum likelihood method to elucidate the genetic diversity of the viral isolates.ResultsA total of 19 patients with confirmed SFTS were identified in northwestern Hubei Province in 2024, with a CFR of 31.6% (6/19). Clinical analyses indicated that bleeding, disturbance of consciousness, prolonged activated partial thromboplastin time (APTT), elevated blood urea nitrogen (BUN), and high viral load (≥107 copies/mL) were critical prognostic indicators of disease severity. Maximum likelihood phylogenetic analyses of the L, M, and S gene segments demonstrated that genotype F was the predominant lineage circulating in this region.DiscussionThis study delineates the genomic diversity and genotype distribution of circulating DBV strains, providing insights into viral etiology in northwestern Hubei. Furthermore, specific clinical/laboratory markers may signal adverse outcomes, emphasizing the imperative for symptom recognition and dynamic monitoring of critical laboratory parameters.